A pocket full of kisses - Penn, Audrey, 1947-; Gibson, Barbara (Washington, D.C. : Child & Family Press, 2004)
Chester Raccoon is worried that his mother does not have enough love for both him and his new baby brother.
"The endearing sequel to the New York Times bestseller The Kissing Hand"--Cover.
G6
Keywords: Mother and child -- Fiction; Sibling rivalry -- Fiction; Love -- Fiction; Babies -- Fiction; Raccoon -- Fiction